Hermeneutika dalam Studi Al-Qur'an: Studi Kritis Hermeneutika sebagai Metode Tafsir Al-Qur'an - Muhamad Redho Al Faritzi; Rifki Azkya Ramadhan (PT. Student Rihlah Indonesia, 2025)
This research aims to critically examine the feasibility of hermeneutics as a method of interpreting the Qur'an, while questioning its compatibility with the epistemology of revelation and the standardized and permanent Islamic shari'a system. This research is a qualitative study with a descriptive-analytical approach through a literature study method, namely by examining primary and secondary literature from the classical tafsir tradition and contemporary hermeneutic thought. The results show that hermeneutics has epistemological roots that are not in line with the character of revelation in Islam and has the potential to shift the authority of the meaning of the Qur'an towards interpretative relativism. The novelty of this research lies in its position that not only examines hermeneutics as a method, but also criticizes it philosophically and methodologically as an interpretive approach that cannot replace the established Islamic interpretive framework. The implication is that the results of this study can be an important consideration in maintaining the authority of tafsir methodology in Islamic education, as well as being an academic policy footing so that Qur'anic studies remain grounded in the integrity of Islamic epistemology.